2009
DOI: 10.1177/0218492309104745
|View full text |Cite
|
Sign up to set email alerts
|

Middle Lobectomy after Pneumonectomy

Abstract: A 59-year-old man underwent a successful middle lobectomy to treat metastasis from a pulmonary adenocarcinoma resected previously by left pneumonectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 4 publications
(8 reference statements)
0
7
0
Order By: Relevance
“…Available data on surgical treatment of the second tumours after pneumonectomy are limited to small series [15][16][17][18][19][20][21][22][23][24][25] or case reports. [26][27][28] In 1-4 cm). The authors observed three deaths (25%) related to treatment, and six patients (50%) required chest tube placement for pneumothorax.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Available data on surgical treatment of the second tumours after pneumonectomy are limited to small series [15][16][17][18][19][20][21][22][23][24][25] or case reports. [26][27][28] In 1-4 cm). The authors observed three deaths (25%) related to treatment, and six patients (50%) required chest tube placement for pneumothorax.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery is even more arduous if the previous resection was pneumonectomy which usually has a significant negative impact on pulmonary reserve. Very few patients undergo additional resection after pneumonectomy, [15][16][17][18][19][20][21][22][23][24][25][26][27][28] and morbidity is not negligible. 20,23 Even a limited resection on the contralateral lung has a negative impact on pulmonary function.…”
Section: Introductionmentioning
confidence: 99%
“…In literature, less than 200 cases of pulmonary resections (lobectomies, segmentectomies, single and multiple wedge resections) after contralateral pneumonectomy were published (4,6,7,12,13,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Most frequently, these were sublobar resections (especially wedge resections) and were performed by thoracotomy without the use of ECLS (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(32)(33)(34). Only a few case reports of ECMO-assisted pulmonary resection after contralateral pneumonectomy exist (4,6,12,13).…”
Section: Single Lung Surgerymentioning
confidence: 99%
“…Evidence of small retrospectives case series suggest that surgery in the remaining lung is a reasonable and rewarding option for well-selected cases. Therefore, these patients should not generally be excluded from an additional surgical approach (4,6,7,12,13,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)72).…”
Section: Additional Pulmonary Resection After Pneumonectomymentioning
confidence: 99%
See 1 more Smart Citation